Physiological declines in sex steroid exposure in relation to changes in body composition in healthy men - a prospective cohort study - Banica, Thiberiu; Verroken, Charlotte; Reyns, Tim; T'Sjoen, Guy; Fiers, Tom; Kaufman, Jean-Marc; Lapauw, Bruno (European journal of endocrinology, 2023)
Androgen levels decline from early adulthood and decreases are steeper in men with increasing body mass index. It is, however, unclear to what extent changes in other indices of body composition and metabolism associate with changes in sex steroid levels in healthy men. Therefore, this study investigated longitudinal changes in body composition and metabolic health in relation to sex steroid levels in healthy adult men. Longitudinal, population-based study. 676 healthy men aged 24-46 years were measured at baseline and after ± 12 years. Serum sex hormone binding globulin (SHBG) was measured using immuno-assay, testosterone (T), estradiol (E2), dihydrotestosterone using LC-MS/MS, free T and E2 (cFE2) and homeostasis model for insulin resistance (HOMA-IR) were calculated. Grip strength was measured by hand grip dynamometry. Body composition was determined using dual-energy x-ray absorptiometry and peripheral quantitative computed tomography. Mean fat mass (FM), lean mass (LM) and HOMA-IR increased (all p<0.001). Decreasing androgen and SHBG levels were associated with increasing FM, whereas decreasing (cF)E2 levels were associated with decreasing FM (all p<0.005). Decreasing (cF)E2 levels and increasing SHBG levels associated with decreasing LM (all p<0.002). Changes in sex steroid levels and HOMA-IR or grip strength were not interrelated. Aging leads to increases in fat mass indices and insulin resistance, whereas changes in parameters of lean mass are less unequivocal. In healthy adult men physiological changes in sex steroid exposure clearly correlate with changes in adiposity but not so with lean mass, insulin resistance or grip strength.